Change Management Strategy in DPKAD Banten - Rizkiah, Tania Nur; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2013)
In July 2012, Regional Regulation of Banten Province Number 3 Year 2012 about The Establishment of The Provincial Department of Banten was enacted. The regulation mandated changes in Organizational Structure and Work Procedures (SOTK) in Department of Finance and Regional Asset Management (DPKAD) of Banten Province, the function of asset management was diverted and DPKAD was turned into Department of Revenue and Finance (DPPKD) of Banten Province. Changes in SOTK were aimed to make a better department’s performance. In transition period to desired condition, there will be a decline in productivity. To minimize the size and the period of declined productivity, the right change management strategy is needed. This study aims to formulate a change management strategy in DPKAD of Banten Province. Data was collected through the distribution of questionnaires to 112 respondents and conducted interviews with 5 of Chief in DPKAD. From the collected data, it was discovered that 4 major restraining forces in DPKAD are fear of losing incentives, problems in system’s synchronization, skepticism, and change the way employees work. 4 major driving forces are mandated in Regional Regulation, job simplification, desire to obtain WTP and develop job performance. In formulating change management strategy, this research used ADKAR model approach, communication strategy, and designing reward system through KPI as performance assessment which is expected to motivate employee to improve their performance.  Keywords :  Change management strategy, Awareness, Desire, Knowledge, Ability, Reinforcement (ADKAR), Key Performance Indicators (KPI)